2021
DOI: 10.21303/2504-5679.2021.001854
|View full text |Cite
|
Sign up to set email alerts
|

IL-1β and IL-10: diagnostic and prognostic potential of cytokines in the assessment of progression of non-alcoholic fatty liver disease in patients with hypertension

Abstract: Non-alcoholic fatty liver disease (NAFLD) affects about a quarter of the world's population and it is closely linked to hypertension (HT). Pro-inflammatory and anti-inflammatory cytokines play a key role in the pathology progression, and the search for non-invasive biomarkers for the diagnosis of NAFLD remains an important issue. The aim of the study was to determine the diagnostic and prognostic value of IL-1β and IL-10 in assessing the progression of liver parenchyma changes in patients with NAFLD and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…NAFLD, affecting a significant portion of the global population and closely linked to hypertension (HT), involves complex interactions of pro-inflammatory and anti-inflammatory cytokines in its pathology. Zhelezniakova et al [ 21 ] showed that IL-1β levels were elevated in the NAFLD and HT group compared to the isolated NAFLD group and control group. Conversely, IL-10 levels were lower in both NAFLD groups compared to the control group.…”
Section: Pathophysiological Aspects Of Interleukins In Nafldmentioning
confidence: 99%
See 2 more Smart Citations
“…NAFLD, affecting a significant portion of the global population and closely linked to hypertension (HT), involves complex interactions of pro-inflammatory and anti-inflammatory cytokines in its pathology. Zhelezniakova et al [ 21 ] showed that IL-1β levels were elevated in the NAFLD and HT group compared to the isolated NAFLD group and control group. Conversely, IL-10 levels were lower in both NAFLD groups compared to the control group.…”
Section: Pathophysiological Aspects Of Interleukins In Nafldmentioning
confidence: 99%
“…Strong relationships were found between CRP, IL-10, and IL-1β levels in patients with NAFLD and HT. Inverse correlations were also observed between IL-10 and IL-1β in patients with NAFLD, both being suggested as potential biomarkers for NAFLD progression [ 21 ].…”
Section: Pathophysiological Aspects Of Interleukins In Nafldmentioning
confidence: 99%
See 1 more Smart Citation